Optimization of Turning Parameters for Cortical Ti-6Al-4V ELI Screw Production Using Taguchi Method - Yulius Riansa Priyusdito; Ahmad Rosibi; Gusri Akhyar Ibrahim; Yanuar Burhanuddin (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2026)
Titanium alloys are widely used in biomedical applications, particularly orthopedic implants. Cortical screws with shallow threads (ISO 5835) require high precision to ensure clinical reliability. This study investigates the machining of Ti-6Al-4V ELI cortical screws using a turning process with carbide tool at cutting speeds of 1.13, 1.98, and 2.83 m/min and depths of cut of 0.1, 0.2, and 0.3 mm. Screw dimensional accuracy was evaluated in terms of height, pitch, α-angle, and β-angle errors. Data analysis employed the Taguchi L9 orthogonal array and signal-to-noise ratio with the “smaller-is-better” criterion. Results indicate that depth of cut is the most influential parameter, significantly affecting all dimensional errors. The optimal condition minimized screw deviations, though surface roughness and fractures at thread peaks were observed. These findings highlight the critical role of depth of cut in achieving ISO-compliant screw quality, with implications for improving the reliability of orthopedic implants.